Risk Profiles Associated with Endometriosis among Infertile Women (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Endometriosis is a common gynaecological disorder which is found in about5% of women and in 30% of infertile women. Identification of risk factors and timely interventionis useful.Methods: A case control study was conducted in the Dept. of obs & gynae of BangabandhuSheikh Mujib Medical University, Shahbag, Dhaka, from October 2015 to March 2016 on50 infertile patients attending the Infertility unit of the institute with the objective to determinethe risk factors of endometriosis. Twenty five women with endometriosis was taken ascases (group-I) and twenty five women without endometriosis was taken as controls(group-II).Result: The mean age was 32.8±5.4 years in group I and 35.1±5.7 years in group II which issimilar. Urban residents were 3.21 times (with 95% CI 0.87-12.71%) more likely to developendometriosis than rural resident which was statistically significant (p0.05) . There was notstatistically significant difference (p>0.05) between two groups in OCP use (84%vs80%).Women with endometriosis had less physical activity than the women without endometriosis;the differences was statistically significant (p